Answer:
x = -8
Step-by-step explanation:
y = 3x + 14
2x - 3y = -14
So, what is the substitution? Y of course, this is because y is equal to 3x + 14.
2x - 3 (3x + 14) = -14
Multiply 3 with the numbers in the parentheses.
2x - 9x + 42 = -14
So you maybe be wondering why it is a negative 7 instead of subtracting 9 with 2. Using PEMDAS, we always read from left to right. So it is basically 2 -9 and you get -7.
-7x + 42 = -14
Then subtract 42 from both sides.
-7x + 42 - 42 = -14 - 42
Simplify
-7x = -56
Divide 7 by both sides.
-7x / 7 = -56 / 7
x = -8
And you might ask, why we get x instead afterwards. This is because both -7 and 7 cancel each other out leaving us with x.
Answer:
2
Step-by-step explanation:
The function shows a point at 2 where x = 0.
Answer:
The first and last one!!
Step-by-step explanation:
Was it correct?? Hope this helps!!(¬_¬ )
Hello
the answer to this is
650
becomes we subtract
88 from 738
738-88 and we get 650
so we get
650
hope this helps